Sports Games towards Intelligence and Nerve Development of Children in Iodine Deficiency Endemic Area - Noor, Zulkhah; Safira, Ira; Darmawati, Idiani (Basic and Applied Nursing Research Journal, 2023)
Increased circulation, hormones, and energy metabolism due to exercise are thought to have a positive effect on nerve growth and development. This study aims to examine the effect of addition of sports games on IQ score, TSH, and BDNF levels of elementary school children in IDD endemic areas. This research method was a quasi-pretest-posttest control group design experiment. As many as 40 children aged 9 -11 years were divided into 19 children as controls, and 21 children doing sports games for 30 minutes per day, five times a week for eight weeks. Serum TSH and BDNF levels were measured using ELISA and IQ score using Culture Fear Intelligence Test (CFIT) method. Statistical analysis used was T-test, Wilcoxon, and Mann-Whitney test. The mean of serum TSH levels and IQ scores of the treatment group were not significantly different from those of the control group (p>0.05). The mean of BDNF levels in both groups increased significantly, and the increase in BDNF levels in the treatment group was greater than in the control group (p<0.05). It can be concluded that the addition of sports games did not significantly change TSH levels and IQ scores (p>0.05), but significantly increase BDNF levels (p<0.05).